CULTURAL APPROACH IN SHAPING THE READINESS OF FUTURE EDUCATORS FOR CREATIVE ARTISTIC AND CONSTRUCTIVE ACTIVITY WITH PRESCHOOLERS - Boryn, Galyna (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the analysis of the ethno-aesthetic component of the cultural approach in the process of preparation of future educators for the management of creative artistic and constructive activity of preschool children. Particular attention is paid to the fact that improving the training of future educators for the upbringing of preschool children is related to the revival of the cultural and educational mission of a higher education institution, establishing those educational relationships that provide for the unity of forms, methods and means of spiritual and creative development of future teachers. It is emphasized that the basis of the cultural approach is the system of value attitude to the social environment, to itself. In modern pedagogical science, the cultural approach is a methodology, which is based on the pedagogy of humanism, it involves the formation of a future personality in the relevant historical and cultural conditions of life, development, education. It has been found that the preparation of future educators of preschool education institutions is a permanent edging process, the content of which is agreed by ukrainian society. At the heart of this process - customs and traditions of the лkrainian people, orientation on national models of folk art. It is clarified that the aesthetization of the educational process in the higher education institution is focused on the use of those forms and methods that contribute to the formation of pedagogical culture of the applicant with the means of art. Ukrainian folk art, penetrating the content of students' learning, provides opportunities for the comprehensive harmonious development of the future tutor, promotes the realization of his creative potential. The procedures for the implementation of the ethno-aesthetic component of the cultural approach during the artistic and constructive activity of education applicants in higher education with the activation of the following characteristics are considered: integrity and sub-sensory (hypersensitivity) of the perception of the world, synergy, imagery, association, sensitivity. Keywords: cultural approach, artistic and constructive activity, educational process, preschool education institution, ethnosthetic component, professional training, higher education institution, education applicants, preschool children.